Adsorption of Methylene blue onto Cajeput Tree Bark: Isotherm and Kinetic Studies - Sukpreabprom, Hatairat; Thongkham, Ratchanee; Thaweepornkul, Phattra (Naresuan University Journal: Science and Technology (NUJST), 2020)
Cajeput tree bark was used as a low-cost adsorbent for the removal of methylene blue from aqueous solutions. The effects of pH, contact time and initial methylene blue concentration on adsorption capacity were studied in batch experiments. The experimental results indicated that the optimum pH for methylene blue adsorption was 7 and the adsorption equilibrium was achieved within 90 minutes. Equilibrium adsorption data were analyzed using Langmuir and Freundlich isotherms. The Langmuir isotherm fitted the equilibrium data better than the Freundlich isotherm. The maximum monolayer adsorption capacity of cajeput tree bark was found to be 64.43 mg/g. The pseudo-first-order and pseudo-second-order kinetic models were selected to describe the adsorption mechanism. Kinetic studies revealed that the adsorption kinetics of methylene blue followed the pseudo-second-order kinetic model. These results showed that cajeput tree bark can be used as an efficient low-cost adsorbent for the removal of methylene blue from aqueous solutions. Keywords: Adsorption, Methylene blue, Cajeput tree bark, Langmuir isotherm, Freundlich isotherm, Adsorption kinetic